TANGGAPAN MASYARAKAT TENTANG HADIRNYA PERTAMBANGAN ASPAL DI DESA WINNING KECAMATAN PASARWAJO KABUPATEN BUTON - Ali, Muhammad Rajif (Jurnal Penelitian Pendidikan Geografi, 2018)
This study aims to describe the public perception of the existence of asphalt minning in relation to the environmental inpact caused in the Winning Vilage of Pasar wajo Distric in Buton District. This research is descriptive qualitative whit case study approach. Data collection is done by using method: questionare, interview, observation and documentation. Data obtained from 55 respondents, then presented in tabular from percentage, then described qualitatively. The result showed that the public response about the presence of asphalt mining in Winning Vilage, divided into positive and negative impacts. Positive impacts of asphalt mining such as: increased local income, creation of employment opportunities for local communities, exposure of territories from isolason. While the negative impact is asphalt mining activities caused environmental damage include: 1) land danmage, land disruption, 2) Damage to flora and fauna, communities responding to asphalt mining activities caused damage to vegetation and people responded to asphalt mining activities causing damage/wild animal/wildlife, 3) The contamination river water, times and swamps where people respond to the mining activitie of asphalt cause pollution of riverwater/times and swamps, 4) Air pollution mainly dust produced from the development process and the means of transportation passing by, 5) Noise, where people respount to asphalt mining activities generate noise, 6) The existence of healt problems where people respoud to asphalt mining activities cause public health problems,